Southern House Mosquito Culex quinquefasciatus Say - Stephanie Larrick; C. Roxanne Rutledge Connelly (EDIS)
EENY457, a 6-page illustrated fact sheet by Stephanie Larrick and Roxanne Connelly, is part of the Featured Creatures collection. It describes this medium-sized brown mosquito that exists throughout the tropics and the lower latitudes of temperate regions and is a vector of many pathogens, several of which affect humans — synonymy, distribution, description, life cycle, medical importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, November 2009.